Cyberpolitik - Munadhil Abdul Muqsith (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:The internet developed for the first time in Indonesia in the early 1990s. Starting from the pagayuban network, it is now expanding without boundaries anywhere. A survey conducted by the Indonesian Internet Service Providers Association (APJII) said that the number of internet users in Indonesia in 2012 reached 63 million people or 24.23 percent of the country's total population. Next year, that figure is predicted to increase by close to 30 percent to 82 million users and continue to grow to 107 million in 2014 and 139 million or 50 percent of the total population in 2015. million people. This matter also results in political communication with the internet media, or is often said to be cyber politics. Cyber politics in Indonesia has faced growth in recent years. There are many facilities that support the growth of cyber politics, such as Facebook, Twitter, mailing list, YouTube, and others.Keywords: Cyberpolitik, Internet Abstrak:Internet berkembang pertama kali di Indonesia pada awal tahun 1990-an. Diawali dari pagayuban network kini berkembang luas tanpa batas dimanapun juga. Suatu survei yang diselenggarakan Asosiasi Penyelenggara Jasa Internet Indonesia (APJII) mengatakan kalau jumlah pengguna internet di Indonesia tahun 2012 menggapai 63 juta orang ataupun 24,23 persen dari total populasi negeri ini. Tahun depan, angka itu diprediksi naik dekat 30 persen jadi 82 juta pengguna serta terus berkembang jadi 107 juta pada 2014 serta 139 juta ataupun 50 persen total populasi pada 2015. juta orang. Perihal ini pula berakibat pada komunikasi politik dengan media internet, ataupun kerap diucap dengan cyber politic. Cyber politic di Indonesia hadapi pertumbuhan sebagian tahun terakhir. Banyaknya fasilitas yang menunjang pertumbuhan cyber politic semacam terdapatnya facebook, Twitter, mailing list, youtobe, serta lain-lain.Kata Kunci: Cyberpolitik, Internet